Pengaruh Budaya Organisasi Sekolah Terhadap Kinerja Guru di SMA NEGERI di Sumatera Utara - Annisa Annisa; Ansari Fahmi; Khadijah Pasaribu; Supardi Situmorang; Yusnia Meha (JURNAL EDUKASI NONFORMAL, 2023)
This study aims to determine the organizational culture in public high schools in Medan, to determine the performance of public high school teachers and to find out whether there is an influence of organizational culture on teacher performance in state high schools in Medan. . This research was conducted at SMA Negeri 1 Kuala Selatan, Labura which consisted of 7 respondents. This type of research used is quantitative research. Methods of data collection using interviews, observation and distribution of questionnaires. The results showed that communication and teacher content had a positive and significant effect on teacher performance.